Breast cancer in the Ashkenazi Jewish population of South Africa: some psychosocial issues - De Vos, Cheryl Lisa (My University, 2014)
Specific mutations in the breast cancer susceptibility genes 1 and 2 (BRCA1 and BRCA2) have been found to be the cause of breast cancer (BRCA) in about 20% of cases in the Jewish population. Affected women often experience a variety of emotional and social issues, which need to be addressed. The aim o f this study was to investigate some o f the psychosocial issues associated with BRCA, the knowledge o f and feelings about it, its treatment and screening strategies, and attitudes to genetic testing in Ashkenazi Jewish women. The subjects were women aged > 18 years with BRCA (30 subjects, Group A),or who had an affected first-degree relative (FDRs) (9 subjects, Group B), or without a family history of BRCA (30 controls, Group C). They were ascertained from the Genetic Counselling files held at the South African Institute for Medical Research (SAIMR), the Medical Oncology Centre o f Rosebank, Johannesburg, the Reach for Recovery organisation, the patient network, or, in the case o f the controls, from the records of the Union of Jewish Women (UJW). A schedule o f questions was specifically constructed (and checked in a pilot study) for use in this study and the Beck Depression Inventory (BDI) was selected to measure depression. A face-to-face interview was conducted with each subject and the schedule and BDI were completed. The average age of the subjects was 57 years, 36 years and 52 years in groups A, B and C respectively. The average age o f Group A subjects at diagnosis was 48.7 years and all had had surgery. The subjects' knowledge of the genetics of BRCA scored between moderate and good. Many Group B subjects overestimated the lifetime risk of developing BRCA. Almos. half (46.7%) the Group A women reported shock as the dominating emotion after diagnosis and they were very concerned that their children would develop the condition (43.3%) or that the cancer would metastasise (26.7%). Only 13 (26.5%) of the medical practitioners involved in the care of the Group A subjects in this study discussed emotional issues with their patients.The group B subjects, after the diagnosis was made in a relative, reported fear of developing BRCA (5), fear o f dying o f the disease (5), and feeling out of control (4).Most subjects (87%) felt that women with BRCA and their relatives would benefit from professional counselling. Less than 25% of subjects in all groups undertook regular breast self-examination (BSE), but one-third of group A subjects discovered a lump themselves.Medical practitioners recommended mammograms in older women to all Group B subjects and most (76%) o f the Group C subjects. However, regular CBE and BSE were only recommended rarely. Half the Group A and Group B subjects stated that they would request genetic testing if it were available locally, mostly to determine whether their children were at risk, or, in the case of FDR's, whether they should improve their vigilance. In order for holistic treatment to be given to affected women and their relatives’ psychosocial and genetic counseling issues should be addressed. Also, the findings suggest that women require further education on the importance o f using available screening strategies for the condition and on the possibility o f genetic testing for BRCA susceptibility in high-risk families. However, such testing needs to be carefully supported and monitored to prevent or ameliorate any adverse psychological or social responses.The study has given an insight into the knowledge of BRCA genetics, the emotional burden, and attitudes to screening and testing possibilities, associated with BRCA in the local Ashkenazi Jewish population.